2020
DOI: 10.1155/2020/8180261
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic Potential of Rhodomyrtone on Human Chondrosarcoma SW1353 Cells

Abstract: Chondrosarcoma is primary bone cancer, with the forceful capacity to cause local invasion and distant metastasis, and has a poor prognosis. Cancer metastasis is a complication of most cancers; it is one of the leading causes of cancer-related death. Rhodomyrtone is a pure compound that has been shown to induce apoptosis and antimetastasis in skin cancer. However, the inhibitory effect of rhodomyrtone on human chondrosarcoma cell metastasis is largely unknown. Effect of rhodomyrtone on cell viability in SW1353 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Successful cancer treatment can be achieved by utilizing the proper antioxidant inhibitors and/or free radical-producing agents. In addition to aryl phloroglucinol, flavonoids, tannins and triterpenes, this plant extract has numerous advantages for cell repair [24][25][26] . The molecular and cellular effects of PDGF inhibition in cervical cells were examined using microarray technology, which revealed changes in gene expression brought on by PDGF silence 27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Successful cancer treatment can be achieved by utilizing the proper antioxidant inhibitors and/or free radical-producing agents. In addition to aryl phloroglucinol, flavonoids, tannins and triterpenes, this plant extract has numerous advantages for cell repair [24][25][26] . The molecular and cellular effects of PDGF inhibition in cervical cells were examined using microarray technology, which revealed changes in gene expression brought on by PDGF silence 27 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that antioxidants help lessen the hazardous side effects of cancer treatment 25 . Antioxidantcontaining plants, such as Rhodomyrtus tomentosa, have been linked to effective cancer treatment with low side effects, which is the basis for the antioxidant intervention 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SW1353 cell line (ATCC, USA) was first separated from a primary chondrosarcoma of the right humerus of a 72-year-old Caucasian female [ 34 ]. Due to resembling chondrocytes phenotypically, SW1353 cells were often applied to exploring the mechanisms of OA [ 35 ].…”
Section: Methodsmentioning
confidence: 99%